Analyzing the Application of The Global Virtual Team (GVT) Model in Developing International Business Skills in Indonesia Higher Education - Liem Gai Sin; Stevi Jimry Poluan (AIBPM Publisher, 2018)
At this time the Global Virtual team (GVT) is widely used in various fields and is common in the business world to work together in teams using online media. Previous studies found some benefits of using internet technology by engaging in a GVT for business institutions include reducing travel costs, increasing innovation and helping local companies penetrate global markets. Previous research shows that the success of doing business in the international business environment can be achieved through good dialogue and collaboration between cultures. By looking at the tendency that business actors are involved in the GVT, the researchers intend to create a learning model based on the GVT model. The developed model of the GVT model is a prototype of the modern business world that is relevant to prepare students for the competencies that needed in the international workforce. Keywords: global virtual team, international competency, education, international business